Biliary Disease : From Science to Clinic - Hirschfield, Gideon; Adams, David; Liaskou, Evaggelia (Springer International Publishing : Imprint: Springer, 2017)
This book addresses the current understanding of the diagnosis and management of biliary disease across all ages, with emphasis on how the latest advances in clinical science may be integrated into current and future therapies. The coverage is wide ranging, encompassing congenital and acquired conditions including cholestatic syndromes, biliary atresia, drug-induced cholestasis, primary biliary cholangitis/cirrhosis, primary sclerosing cholangitis, cholangiocarcinoma, gallstone disease, and autoimmune sclerosing cholangitis. With contributions from basic and clinical scientists, the relevance of state-of-the-art mechanistic biology to diagnosis, treatment, and future opportunities for drug design is clearly explained. The balance between science and clinical practice will ensure that this book makes a lasting contribution to the field. A broad readership will find the book easy to access and a rich source of information on current best practice and evolving management strategies.
Keywords: Medicine.; Radiology.; Gastroenterology.; Hepatology.; Nursing.; Pathology.; Pediatrics.; elektronické knihy; electronic books